Bridging Education and Sustainable Development: Assessing Future Psychologists’ Perspectives - Stoliarchuk, Olesia; Liang, Keyan; Khrypko, Svitlana; Ishchuk, Olena; Serhieiеnkova, Oksana; Kalishchuk, Svitlana; Divchuk, Tetiana (European Journal of Sustainable Development, 2023)
Education serves as a dynamic interplay between generations, encompassing dialogue and mutual enrichment. It embodies the spiritual essence inherent in individuals, communities, eras, and cultural contexts, shaped by moral and spiritual values specific to cultural circles. Education bridges the gap between the ‘values of the environment’ and the ‘values of life experience’, defining the persona of individuals, communities, and societies. It functions as a repository of intellectual potential, dismissing the notion of ‘excessive’ education and highlighting its indispensability for human growth. Values, pivotal to human intellectual exploration, encapsulate the initiation, propagation, or negation of philosophical paradigms within fluctuating contexts. Education emerges as a distinctive manifestation of self-cultivation and a testament to human accomplishments. This study aimed to assess sustainable social development awareness and implementation readiness among future psychologists. The investigation involved 160 Ukrainian psychology students, employing written surveys and statistical analysis. Findings unveiled a limited comprehension of sustainable societal development among respondents, often narrowed to environmental concerns and overlooking the social facet. Despite this, over half of the participants sought alignment with their interpretation, integrating these ideals into their university environment. The ongoing conflict in Ukraine intensified the urgency of instilling sustainable development values, though a third of the respondents fully embraced these concepts. Implementation challenges included consumeristic attitudes towards natural resources and low environmental consciousness, highlighting the need for value propagation and social responsibility cultivation. Respondents recognized the social dimension’s salience in their future professional roles, albeit with a tendency to overlook intergenerational continuity concerns. The study exposed limited and fragmented competence in understanding sustainable societal development among future psychologists, with value cultivation appearing spontaneous and disjointed. The university environment presents an opportunity to nurture sustainable development values, urging educators to augment students’ competency and motivational preparedness for their roles in implementing these concepts. Keywords: sustainable development, education, values, future psychologists, professional training, awareness, societal progress, professional roles.